THE IMPACT OF INFLUENCERS ON PERSONAL FINANCIAL MANAGEMENT WITH PRODUCT PURCHASING DECISIONS AS A MEDIATING VARIABLE - Solikhah, Adhifatus; Vera Dwi Inazarina (Count : Journal of Accounting, Business and Management, 2024)
The advancement of internet technology has increased the number of social media users in Indonesia, especially among Generation Z. This phenomenon encourages business actors to utilize influencer-based marketing strategies to attract consumer attention and increase purchasing decisions. However, massive promotions through influencers can also trigger consumer behavior that has the potential to disrupt personal financial management. This study aims to analyze the influence of influencers on personal financial management with purchasing decisions as a mediating variable. This study uses a quantitative approach with an explanatory design. Data were collected through a closed questionnaire based on a Likert scale distributed to 100 respondents aged 15–44 years using a stratified random sampling technique. Data analysis was carried out using the Path Analysis method with the help of SPSS software. The results of the study showed that influencers have a positive influence on product purchasing decisions and personal financial management. However, influencers through product purchasing decisions have a negative effect on personal financial management. So it can be concluded that the results of this study are that influencers have an influence on personal financial management without the role of product purchasing decisions as a mediating variable. These findings indicate that although influencers are able to increase purchasing decisions that can directly support financial management, interactions through purchasing decisions can actually worsen personal financial management in some conditions. This may be due to consumer behavior driven by influencer promotions, which ultimately over-influences purchasing decisions and reduces the effectiveness of individual financial management.